Competition between rhythmic and linguistic organization in a sentence-rhythm Stroop task. Issue 11 (November 2015) - Getz, Laura M.; Salona, Priyanka; Yu, Minhong; Kubovy, Michael
We provide a test of Patel's [(2003). Language, music, syntax and the brain. Nature Neuroscience, 6, 674–681] shared syntactic integration resources hypothesis by investigating the competition between determinants of rhythmic parsing and linguistic parsing using a sentence-rhythm Stroop task . We played five-note rhythm patterns in which each note is replaced with a spoken word of a five-word sentence and asked participants to indicate the starting point of the rhythm while they disregarded which word would normally be heard as the first word of the sentence. In Study 1, listeners completed the task in their native language. In Study 2, we investigated whether this competition is weakened if the sentences were in a listener's non-native language. In Study 3, we investigated how much language mastery is necessary to obtain the effects seen in Studies 1 and 2. We demonstrate that processing resources for rhythmic parsing and linguistic parsing overlap with one another, particularly when the task is demanding. We also show that the tendency for language to bias processing does not require deep knowledge of the language.